Cosmetic usage: understanding how major determinants are affecting users / Norudin Mansor, Desnika Efni Mat Ali and Aisya Ibrahim - Mansor, Norudin; Mat Ali, Desnika Efni; Ibrahim, Aisya (2008)
Studies on cosmetics have received more attention not only from the users, producers, retailers, but also from the authorities who are governing the industry. The impact of the product usage received great attention but the understanding of its development is hardly explored. Regardless of this, from year to year, the sales of cosmetics demonstrated continued growth. The industry nowadays has diversified its marketing approach not only to the traditional female market, but also to male market as well. A survey was conducted involving 622 respondents from the public of the East Coast of Malaysia. The survey was on the effect of cosmetic usage to the skin. The survey adopted a personally administered questionnaire. Specifically, the survey included three constructs such as branding, ingredients, and its effect on skin which are assumed to be among the primary determinants of cosmetics. The study further investigated several demographic profiles as to what extend it influences the usage of cosmetics. Finding of the study using correlation and regression analysis indicated that there was a significant relationship between the identifiable constructs as to the determinant for the purchase and usage of cosmetic.